2021
DOI: 10.3233/thc-219008
|View full text |Cite
|
Sign up to set email alerts
|

Classification and action rules in identification and self-care assessment problems

Abstract: BACKGROUND: Disability, especially in children, is a very important and current problem. Lack of proper diagnosis and care increases the difficulty for children to adapt to disabilities. Disabled children have many problems with basic activities of daily living. Therefore, it is very important to support diagnosticians and physiotherapists in recognizing self-care problems in children. OBJECTIVE: The aim of this paper is to extract classification and action rules, useful for those who work with children with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Furthermore, the QSAR application focused on basic calculation and feedback while using the prediction model of a single algorithm only. Kwon and Zdrodowska found that using a single model did not elicit impressive results when the response characteristics of each subject were collected; however, the most important predictors could be identified by combining multiple models [ 23 , 29 ]. This study’s main algorithm was a basic artificial neural network.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the QSAR application focused on basic calculation and feedback while using the prediction model of a single algorithm only. Kwon and Zdrodowska found that using a single model did not elicit impressive results when the response characteristics of each subject were collected; however, the most important predictors could be identified by combining multiple models [ 23 , 29 ]. This study’s main algorithm was a basic artificial neural network.…”
Section: Discussionmentioning
confidence: 99%